2016
DOI: 10.1016/j.fct.2016.01.012
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a low iron diet and early life methylmercury exposure in Daphnia pulex

Abstract: Iron (Fe) deficiency increases risk for adverse health outcomes in humans; however little is known about the potential interaction with methylmercury (MeHg) exposure. Studies testing multiple stressor hypotheses are expensive and time consuming in mammalian model systems; therefore, determining relevance of alternative models is important. Daphnia pulex were fed standard or low-Fe diets of freshwater algae, Ankistrodesmus falcatus. MeHgCl (1600 ng/L) or vehicle was added to culture media for 24 h during early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…ranging from daphnids (Demott & Muller-Navarra, 1997;Elendt & Bias, 1990;Gregor et al, 1991;Hudson et al, 2016) to Xenopus (Fort et al, 1999;Fort & Schlekat, 2002). Overall, the present study demonstrated that the SMN benchmark provides a good representation of feeding conditions provided by the natural habitat of X. laevis.…”
Section: Thyroid Gland Histopathologymentioning
confidence: 65%
See 1 more Smart Citation
“…ranging from daphnids (Demott & Muller-Navarra, 1997;Elendt & Bias, 1990;Gregor et al, 1991;Hudson et al, 2016) to Xenopus (Fort et al, 1999;Fort & Schlekat, 2002). Overall, the present study demonstrated that the SMN benchmark provides a good representation of feeding conditions provided by the natural habitat of X. laevis.…”
Section: Thyroid Gland Histopathologymentioning
confidence: 65%
“…However, with strict consideration of studies performed in the laboratory, we hypothesize that the slower‐than‐natural rates of metamorphosis in the previously discussed laboratory‐based studies (Balch et al, 2006; Carr et al, 2003; Conners et al, 2009; DuPreez et al, 2008; Goleman et al, 2002; Goleman & Carr, 2006; Hu et al, 2006; Plowman et al, 1994; Sharma & Patiño, 2009) likely resulted from the inadequate nutritional quality of the diet. Historically, nutritional deficiencies in standard laboratory‐based populations have been identified ranging from daphnids (Demott & Muller‐Navarra, 1997; Elendt & Bias, 1990; Gregor et al, 1991; Hudson et al, 2016) to Xenopus (Fort et al, 1999; Fort & Schlekat, 2002). Overall, the present study demonstrated that the SMN benchmark provides a good representation of feeding conditions provided by the natural habitat of X. laevis .…”
Section: Discussionmentioning
confidence: 99%